LGG-46. MOLECULAR CHARACTERIZATION OF HEMISPHERIC LOW-GRADE GLIOMAS IN CHILDREN. (4th December 2020) - Mišove, Adéla; Krsková, Lenka; Sumerauer, David; Zámečník, Josef; Váňová, Kateřina; Starý, Jan; Perníková, Ivana; Vícha, Aleš; Libý, Petr; Tichý, Michal; Táborský, Jakub; Kynčl, Martin; et al.
Abstract: BACKGROUND: Heterogeneous pathology in hemispheric low-grade gliomas (hemLGG) stress the importance of molecular testing in terms of prognosis prediction and targeted therapy options. METHODS: Demographic data was collected and targeted genomic approach was employed in the single institutional study. RT-PCR was used to screen for KIAA1549-BRAF fusion and FGFR1 tyrosine-kinase domain duplication (FGFR1-ITD). Direct sequencing evaluated point mutations (BRAF ex15 and ex11, FGFR1 ex12 and ex14). Samples with no detected alteration were subjected to panel RNA-sequencing (FusionPlex Archer Diagnostics). RESULTS: Within 2000–2019 were diagnosed 76 patients with hemLGG (median age 11.1y, range 0.0y–18.5y) comprising predominantly of ganglioglioma, dysembryoplastic neuroepithelial tumors, and diffuse astrocytoma. 40 % of hemLGG were characterized by BRAF alterations with over 2/3 of those cases harboring BRAF point mutations (two BRAFex11, 12 BRAFV600E). Notably, BRAF fusions were uncommon and detected only in six patients (two KIAA-BRAF fusion, two minor oncogenic BRAF variants, two non-KIAA BRAF fusion). 25 % of alterations were found in genes for receptor tyrosine kinases, consisting of seven patients with FGFR1-ITD, three FGFR2/3 fusions, two FGFR1 mutations, two ALK fusions, and one ROS fusion. Out of MAP kinase pathway, the most frequent alteration was IDH1 mutations (n=9). Two angiocentric gliomas were characterized by MYB-QKI fusion. CONCLUSION: Targeted sequencing combined with RNA-sequencing is feasible to establish molecular diagnosis in majority of cases and reveal new and rare alterations. Significant prevalence of non-BRAF alterations explains heterogeneity among hemLGG.